PERANAN PROMOSI DAN PLACE BRANDING DALAM MENINGKATKAN REPURCHASE INTENTION WISATA KULINER BAGI WISATAWAN DI KOTA BANDUNG DAN SEKITARNYA - Utarsih, Henny (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2019)
The purpose of this study was to find out discussion of promotion implementation, description of place branding, description of repurchase intention, simultaneous promotion and partial promotion and place branding on tourist culinary repurchase intentions in Bandung and its surroundings.The object of this research is domestic tourists who have visited Bandung and its surroundings. As a research method using survey methods with descriptive and verification analysis. Data sources used are primary and secondary. Determination of the sample is done by purposive sampling. Data collection techniques were carried out through questionnaires, interviews, observations, and literature studie. The results of research are included in the good category, where branding is included in the very good category. The purpose of culinary repurchases for domestic tourists in the city of Bandung and its surroundings is included in the excellent category. Promotions and branding venues that focus on culinary repurchase intentions in the city of Bandung and surrounding areas. Keywords: promotion, place branding, intention to buy back, culinary tourism.